2127. The Role of Prophylactic Antibiotics for Reducing Infections Following Knee Arthroscopy. (26th November 2018) - Safdar, Nasia; Shaughnessy, Catherine; Musuuza, Jackson; Pop-Vicas, Aurora
Abstract: Background: Surgical site infections (SSI) following arthroscopy are associated with considerable morbidity. Whether antibiotic prophylaxis can reduce the risk of SSI following knee arthroscopy is unclear. Methods: We undertook a meta-analysis of studies comparing incidence of SSI in patients receiving antibiotic prophylaxis vs. no antibiotics before undergoing knee arthroscopy. We searched multiple computerized databases; data were pooled using a random effects model. We excluded knee arthroscopy studies for which the distribution of patients receiving antibiotics vs. no antibiotics was unavailable. CDC definitions for SSI were used to determine incidence of infection. Results: Five retrospective studies including 47, 548 patients met inclusion criteria; none were randomized trials. The risk of SSI in the prophylactic antibiotic group was 0.38% and in the no antibiotic group was 0.37% (pooled OR 0.99, 95% CI 0.69–1.42). There was no statistical heterogeneity. Conclusion: The evidence to date, which is limited to retrospective studies, suggests no difference in SSI incidence with and without antibiotic prophylaxis for knee arthroscopies. Prospective studies are required to further evaluate this finding. Future research should evaluate whether antibiotic prophylaxis prevents SSI in other joint arthroscopy procedures, such as shoulder arthroscopy. Disclosures: All authors: No reported disclosures.